Clinical characteristics and management of hemodialysis patients with pre-dialysis hypertension: a multicenter observational study. Issue 1 (31st December 2022) - Liang, Yaoxian; Gan, Liangying; Shen, Yulan; Li, Weihua; Zhang, Dongliang; Li, Zhongxin; Ren, Jianwei; Xu, Mingcheng; Zhao, Xiaolin; Ma, Yingchun; Zuo, Li; Wang, Mei
Abstract: Background: Hypertension is a leading preventable risk factor for cardiovascular disease in hemodialysis patients. Pre-dialysis systolic blood pressure (SBP) more than 160 mmHg was thought to be associated with increased risk of cardiovascular events and all-cause mortality. The present study was performed to explore the clinical characteristics and management of hemodialysis patients with pre-dialysis SBP ≥ 160 mmHg. Methods: A total of 1233 patients undergoing hemodialysis from nine hemodialysis centers were enrolled. Pre-dialysis and home BP were measured and clinical data were collected. The characteristics of patients with pre-dialysis SBP ≥ 160 mmHg were explored. Clinical parameters between hypertensive and non-hypertensive patients were compared. The partial correlation analyses performed to identify the associations between BP and clinical parameters. Results: There were 24.6% of the hemodialysis patients had pre-dialysis SBP ≥ 160 mmHg and the average SBP was 173.8 ± 10.9 mmHg. Only 21.4% of the patients achieved dry weight after dialysis and up to 30.2% of patients were not given combination therapies of antihypertensive drugs. Compared to patients with pre-hemodialysis SBP < 160 mmHg, patients with pre-dialysis SBP ≥ 160 mmHg had lower target-reaching rate of Kt/v and higher incidences of intradialytic hypotension and muscle spasm. Most patients (96%) with pre-dialysis SBP ≥ 160 mmHg had home SBP≥ 135 mmHg. Patients with home SBP ≥ 160 mmHg had higher left ventricular weight index and lower hemoglobin levels when compared to their counterparts with home SBP <160 mmHg. Conclusions: Pre-dialysis SBP ≥ 160 mmHg is common in clinical practice and most of the patients could diagnosed to be hypertensive according to their home SBP. Patients with pre-dialysis SBP ≥ 160 mmHg are more likely to be subjected to dialysis insufficiency and intradialytic complications. Achieving dry weight and sufficient pharmacologic interventions should be strengthened to improve BP control in the hemodialysis population.